An Assessment of Quality Audit Practices with Special Reference to Wipro, Vishakhapatnam (India): Understanding the Significance of Audit Quality in Wipro, Vishakhapatnam (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of this thesis is to give bits of knowledge into what the idea of audit quality methods for various gatherings who have responsibilities for delivering, appointing or evaluating audit quality in practice - auditors, AC individuals and quality controllers concerning. This exploration depends on an interpretive methodology employing research techniques for report analysis, semi-organized meetings and a review survey. Drawing on a symbolic communications system, the exploration illustrates the way toward offering significance to audit quality in practice.